CNReader: a reading practice tool designed for Chinese children with developmental dyslexia - Lijuan Liu; Tuo Fang; Enmao Liu; Shang Shi; Shuo Zhai; Yang Chen; Lingyan Zhang; Yan Shi; Cheng Yao (Humanities & Social Sciences Communications)
Abstract Developmental dyslexia among Chinese-speaking children presents distinct linguistic, cognitive, and information-processing deficiencies, negatively affecting academic performance and cognitive development. Existing dyslexia interventions largely rely on manual guidance, and due to limited resources and a narrow practice approach, results often fall short. This paper presents an innovative tool, CNReader, designed to support reading training for young Chinese children with dyslexia. Incorporating user-friendly visual text presentation, personalized reading guidance, and artificial intelligence (AI) reading support, CNReader aims to stimulate and enhance children’s reading interest and ability. Our study engaged children with mild dyslexia across three experimental phases. Results demonstrated that CNReader significantly reduced reading error rates, enhanced reading fluency, and improved comprehension. Notably, AI-paired reading emerged as both more appealing to children and more effective than conventional human-assisted approaches. Furthermore, following a 1-month training period, participants exhibited marked improvements in reading speed, accuracy, and engagement. This research validates CNReader’s efficacy as an intervention tool for Chinese dyslexia and underscores the potential of AI integration in reading assistance technologies designed for children with reading disabilities.